Change processes in relationships : a relational-historical research approach - Fogel, Alan; Garvey, Andrea; Hsu, Hui-Chin; West-Stroming, Delisa (Cambridge University Press, 2006)
Just as each person develops from infancy to adulthood, all interpersonal relationships have a life history that encompasses the changes in how people communicate with each other. This book is about how a relationship transforms itself from one pattern of communication to another. Compelling and innovative, it offers original research.